The Eötvös Torsion Balance Method Of Mapping Geologic Structure (04302329-9c91-4a18-a893-ee8bad936186) - Donald Barton (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1928)
THE theory of gravitation is based on Newton's law that any two bodies exert a mutual attraction which is proportional to the product of their masses and inversely proportional to the square of the distance between them; i. e. A= K MM/R2 (1) where K is a constant, M and m are the respective masses of the two bodies, and R the distance between them. In the earth's gravitational system, the earth is one of the bodies; the other may be any body within or without the earth. In theoretical discussions and calculations in regard to gravity, that other body usually is taken as a unit of mass: in the C. G. S. system, a body of one gram in mass.